Viva Delay - Yahaghi, Hossein; Sorooshian, Shahryar; Yahaghi, Javad (Springer Netherlands, 2017)
The time delay between submission of a thesis and Viva Voce is intolerable for students. This letter tries to draw the readers’ attention to the effect of choosing the right examiner, in order to reduce the Viva Voce delay.